Optimizing the Implementation of Project-Based Learning 21st Century Learning Models for Elementary School Teachers - Elinda Rizkasari; Ani Restuningsih (Jurma : Jurnal Program Mahasiswa Kreatif, 2022)
The purpose of this Community Service activity is to conduct training on the implementation of the 21st Century learning model, namely the Project Based Learning model. This service was carried out at the Wahidin Sudiro Husodo Group, Jumapolo District, Karanganyar, Central Java with 30 participants who were representatives of 8 Elementary School Teachers. The method of implementing this community service activity is the Participatory Action Research method. This Participatory Action Research method consists of the stages of planning (plan), action (action), observation (observe), and reflection (reflection). The results of this community service activity were in making Project Based Learning Implementation Plans (RPP) as many as 88% of participants stated that the training provided was beneficial and those who had not previously implemented the Project Based Learning learning model understood its implementation in learning.